Survey of Accepted Practice following Failed Intubation for Emergency Caesarean Delivery - Daniel Soltanifar; David Bogod; Sally Harrison; Brendan Carvalho; Pervez Sultan (Anesthesiology Research and Practice)
Background. There is no consensus on the optimum management of failed tracheal intubation in emergency cesarean delivery performed for fetal compromise. The decision making process on whether to wake the patient or continue anesthesia with a supraglottic airway device is an underexplored area. This survey explores perceptions and experiences of obstetric anesthetists managing failed intubation. Methods. Anesthetists attending the Group of Obstetric Anaesthetists London (GOAL) Meeting in April 2014 were surveyed. Results. Ninety-three percent of anesthetists surveyed would not always wake the patient in the event of failed intubation for emergency cesarean delivery performed for fetal compromise. The median (interquartile range) of perceived acceptability of continuing anesthesia with a well-fitting supraglottic airway device, assessed using a visual analogue scale (0–100; 0 completely unacceptable; 100 completely acceptable), was 90 [22.5]. Preoperative patient consent regarding the use of a supraglottic airway device for surgery in the event of failed intubation would affect the decision making of 40% of anaesthetists surveyed. Conclusion. These results demonstrate that a significant body of anesthetists with a subspecialty interest in obstetric anesthesia in the UK would not always wake up the patient and would continue with anesthesia and surgery with a supraglottic airway device in this setting.